Wirkung von Sportinterventionen auf die psychische Gesundheit von Jugendlichen: Ein systematisches Review mit Praxisbeispiel Boulderpsychotherapie - Donath, Carolin; Atzmüller, Lukas; Florack, Jakob; Engel, Caroline; Luttenberger, Katharina (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2024)
The Effect of Exercise Therapy on Adolescent Mental Health: A Systematic Review with Practical Example Abstract: The mental health of children and adolescents in Germany is currently highly burdened. Because of the psychotherapeutic care situation, easily accessible, less stigmatizing, and efficient offers are urgently needed. Exercise therapy would be one possibility. However, the effectiveness of such offers must first be proven. We conducted a systematic review concerning the effectiveness of exercise therapy on the mental health of children and adolescents which included studies since 2020 (subsequent to Hale et al., 2021). We analyzed a total of 17 intervention studies based on the PRISMA statement. The results show that exercise therapy interventions significantly affect certain populations: Attention and cognitive skills significantly improved in children and adolescents with ADHD; for depression, we found positive effects for affection. Some studies revealed significant effects across populations on the quality of life and sleep. In children and adolescents with autism or learning disabilities, we found positive effects on social behavior. Thus, according to the literature, exercise therapy is a recommendable therapy option for children and adolescents with mental health problems. As an illustration, we present a boulder intervention as a combined exercise intervention and psychotherapy along with its feasibility as a possible practical example.
EVALuna2:555726